KAITAN GOOD CORPORATE GOVERNANCE DENGAN FINANSIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR TEKSTIL DAN GARMENT DI BURSA EFEK INDONESIA(BEI) PERIODE 2014-2016 - Ni Nyoman Ayu Diantari; I Gst. Ngr. Bagus Gunadi; I Wayan Suarjana (VALUES, 2019)
This study aims to analyze the relationship of good corporate governance to financial distress. Corporate governance mechanisms in this study include managerial ownership, institutional ownership, board size, board of commissioners, independent commissioners, company size and leverage.The sample in this study were 10 textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2016 period. Data obtained by using purposive sampling method from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2014-2016. The method used to analyze the data is the logistic regression method.The results showed that managerial share ownership, institutional ownership and independent commissioners had a negative effect on financial distress, while this study failed to prove the influence of board size, board of commissioners, company size and leverage on financial distress.